2017
DOI: 10.1016/j.bjorl.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative otorhinolaryngologic complications in transnasal endoscopic surgery to access the skull base

Abstract: The use of the nasoseptal flap has revolutionized endoscopic skull base surgery, making the procedures more effective and with lower morbidity compared to the traditional route. However, although mainly transient nasal morbidities were observed, in some cases, permanent hyposmia and anosmia resulted. An improvement in this technique is therefore necessary to provide a better quality of life for the patient, reducing potential complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 38 publications
(53 reference statements)
0
36
0
2
Order By: Relevance
“…Dolci et al found that 10 of 41 patients had signs of hyposmia or anosmia after ESBS . However, no preoperative scores or statistical comparisons were taken, some patients had olfactory groove tumors, and follow‐up time was variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dolci et al found that 10 of 41 patients had signs of hyposmia or anosmia after ESBS . However, no preoperative scores or statistical comparisons were taken, some patients had olfactory groove tumors, and follow‐up time was variable.…”
Section: Resultsmentioning
confidence: 99%
“…Dolci et al found that 10 of 41 patients had signs of hyposmia or anosmia after ESBS. 29 However, no preoperative scores or statistical comparisons were taken, some patients had olfactory groove tumors, and follow-up time was variable. Tajudeen et al focused exclusively on the feasibility of smell preservation after endoscopic unilateral resection of esthesioneuroblastoma, and showed that eight out of 14 patients were able to preserve some olfaction on UPSIT testing after surgery.…”
Section: Qualitative Summarymentioning
confidence: 99%
“…Cheng et al . had only 1 (0.8%) septal perforation in a cohort of 129 patients who underwent endoscopic transnasal transsphenoidal surgery, whereas Dolci et al . reported internal nasal valve collapse in 6 (14.6%) patients and no septal perforations in a cohort of 41 endoscopic transnasal transsphenoidal surgery patients.…”
Section: Complicationsmentioning
confidence: 99%
“…Unauthorized distribution is strictly prohibited. Conger et al 33 2018 509 5 (83) 2 (33) 3 (43) 4 (17) 14 (33) Dehdashti et al 34 2016 180 4 (67) 1 (17) 3 (43) 6 (25) 14 (33) Dolci et al 35 This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Limitationsmentioning
confidence: 99%